Traditional uses of medicinal animals in the semi-arid region of northeastern Brazil - Alves Rômulo Romeu Nóbrega; Neta Rita Oliveira de Sousa; Trovão Dilma Maria de Brito Melo; Barbosa Jose Etham de Lucena; Barros Adrianne Teixeira; Dias Thelma Lucia Pereira (BMC, 2012)
Abstract The present work presents an inventory of the traditional medicinal uses of animals in the municipality of Bom Sucesso in Paraíba State (PB) in the semiarid northeastern region of Brazil. Information was obtained through the use of semi-structured interviews with 50 people who use zootherapeutic products. A total of 25 animal species used for medicinal purposes were identified (18 vertebrates and seven invertebrates) distributed among five taxonomic categories; the groups with the largest numbers of citations were: mammals (8 citations), insects (7), and reptiles (5). The most cited animal species were: Tubinambis merianae "teju" lizards (44 citations); Apis mellifera Italian honeybees (318 citations); Gallus gallus chickens (31 citations); Ovis aries sheep (31 citations); Crotalus durissus rattlesnakes (14 citations); Boa constrictor (12 citations); and Bos taurus cattle (12 citations). A significant number of illnesses and conditions treated with animal-based medicines were cited, and the category with the greatest number of citations was "problems affecting the respiratory system". Our results suggest that the use of zootherapeutics in the region is persistent, and that knowledge about these curative practices is an integral part of the regional culture. As such, studies concerning the uses of zootherapeutics are important windows to understanding human/environmental/cultural interactions and a pathway to conciliating regional cultures with efforts to conserve the native fauna.